Femininity, Transgression and the Gothic: the Witches of Cradle of Filth - DOGARU, Rebeca (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
While the aesthetic of the British extreme metal band Cradle of Filth strikes the onlooker with its Baroque flamboyance, its Gothic macabre and underground kitsch, its music – both classically melodious and expressively extreme – immerses the listener into a poetry of Romanticist pastiche spiced with unexpected word-plays, heavy symbolism and cultural references, taboo themes and transgressions of social norms at every level. The weave of apparent contradictions which tailors Cradle of Filth’s distinctive style in contemporary music is also reflected in one of the central themes of the band’s imaginary: the norm-defiant femininity embodied in the image of the witch. This study examines the varied typologies of the female characters of Cradle of Filth’s fiction, their traits as both heroes and transgressors in the context of the Gothic genre and extreme music. My analysis seeks to help fill some gaps in the analysis and understanding of the often misinterpreted music genre of extreme metal, and underline fundamental traits of a representative presence in this field, Cradle of Filth, not in terms of musical or aesthetic theory but of its lyrical value in the context of postmodern literature.